Knowledge and practice of complementary feeding among mothers of the children aged group 6-24 months - Shah, Geeta; Dangol, Anamika; Shah, Naveen Prakash; Joshi, Lok Raj (International Journal Of Community Medicine And Public Health, 2026)
Background: Complementary feeding, initiated at six months of age, is essential to meet the nutritional needs of infants beyond breast milk. Inappropriate complementary feeding practices contribute to malnutrition, increased morbidity, and poor growth outcomes among young children in Nepal. This study aimed to assess the knowledge and practices of complementary feeding among mothers of children aged 6–24 months in Mahalaxmi Municipality, Lalitpur, Nepal. Methods: A descriptive cross-sectional study was conducted among 208 mothers attending Primary Health Care services. Participants were selected using a non-probability purposive sampling technique. Data were collected using a semi-structured questionnaire and analysed using SPSS software using descriptive statistics. Results: The mean age of respondents was 27.10±6.30 years. Most mothers (69.2%) correctly defined complementary feeding, with family members (42.2%) and Female Community Health Volunteers (25.3%) as the main sources of information. Exclusive breastfeeding up to six months was practiced by 52.4% of mothers, while 23.1% introduced complementary feeding before six months. Homemade foods were provided by 83.1% of mothers, and 63.9% continued breastfeeding after initiating complementary feeding. Although hygiene practices were optimal, gaps were observed in feeding timing, food consistency, and feeding during child illness. Conclusions: Despite relatively good knowledge, suboptimal complementary feeding practices persist. Strengthening maternal nutrition education through health workers and community-based interventions is essential to improve child nutrition outcomes.